Screening, isolation and characterisation of antimicrobial/antifungal peptides produced by lactic acid bacteria isolated from wine - Morgan, Joanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.